2016
DOI: 10.1515/chem-2016-0023
|View full text |Cite
|
Sign up to set email alerts
|

Analytical tools for determination of new oral antidiabetic drugs, glitazones, gliptins, gliflozins and glinides, in bulk materials, pharmaceuticals and biological samples

Abstract: Abstract:The review presents analytical methods for determination of new oral drugs for the treatment of type 2 diabetes mellitus (T2DM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 91 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…Based on reports published by International Diabetes Federation, the total number of those suffering from diabetes is growing every year. For instance, according to statistic predictions, type 2 diabetes, currently affecting about 8% of adult population, would spread in such a pace that by 2030, more than 40 million cases can be found throughout the world. Metformin ( N , N -dimethylbiguanide) is a popular glucose-lowering agent that helps type 2 diabetic patients in better insulin performance. …”
Section: Introductionmentioning
confidence: 99%
“…Based on reports published by International Diabetes Federation, the total number of those suffering from diabetes is growing every year. For instance, according to statistic predictions, type 2 diabetes, currently affecting about 8% of adult population, would spread in such a pace that by 2030, more than 40 million cases can be found throughout the world. Metformin ( N , N -dimethylbiguanide) is a popular glucose-lowering agent that helps type 2 diabetic patients in better insulin performance. …”
Section: Introductionmentioning
confidence: 99%
“…The statistically significant value for intravenous and oral administration of (+)-terbutaline was slightly higher than for (−)-terbutaline [63]. pharmacological studies, pharmacokinetic studies, and therapeutic drug monitoring [76][77][78]. Recently, the enantioseparation of chiral pharmaceuticals in the environmental matrices becomes more important.…”
Section: Stereoselective Pharmacokinetics Of β 2 -Agonistsmentioning
confidence: 99%
“…Such sodium-glucose cotransporters are responsible for reabsorbing glucose into the kidney. [2,3] An extensive literature survey has revealed that there are few methods that are reported for estimation of SAXA and DAPA individually or in combination with other drugs by UV method, [4][5][6][7] reverse phase high performance liquid chromatographic (RP-HPLC) method, [8][9][10][11][12][13][14][15][16] tandem mass spectrometry method, [17] or LC-MS. [18,19] Hence, we propose to develop methods that are more reliable, sensitive, and simple for simultaneous estimation of SAXA and DAPA in bulk as well as a pharmaceutical formulation. In the present work, we developed and validated the UV method and RP-HPLC method for the simultaneous estimation of SAXA hydrochloride and DAPA in bulk drug and its formulation as per ICH guidelines Q2(R1).…”
Section: Introductionmentioning
confidence: 99%